Hubungan Antara Risiko Sistematis, Tingkat Suku Bunga, dan Return Saham dalam Portofolio Investasi: Analisis pada Bank BUMN yang Terdaftar di BEI - Banafsyah Imanda Safa; Diana Oktavia Kholimah Wati; Vidinia Nuansa Citra; Felisya Natalia Purwanto; Maria Yovita R. Pandin (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This study aims to examine the impact of systematic risk and interest rates on the stock returns of state-owned banks (Bank BUMN) listed on the Indonesia Stock Exchange during the period 2021–2023. Using a multiple linear regression approach, the study finds that neither systematic risk nor interest rates have a significant partial or joint effect on the stock returns of Bank BUMN. These findings indicate that in the context of the Indonesian stock market—particularly the state-owned banking sector—these factors may not necessarily be the primary determinants in shaping stock returns. The implication of these results is the importance of considering other variables that may play a greater role in explaining stock return movements, such as firm-specific microeconomic factors and investor expectations regarding the banks’ fundamental performance.